Echoing narratives : studies of intertextuality in Greek and Roman prose fiction - Doulamis, Konstantin (Ancient narrative. Supplementum, 2011)
"Intertextuality has been recognised as an important feature of ancient prose fiction and yet it has only received sporadic attention in modern scholarship, despite the recent explosion of interest in the ancient novels. This volume is intended to make a contribution towards filling this gap by drawing attention to, and throwing fresh light on, the presence in ancient Greek and Roman narratives of earlier literary echoes."--